PENGARUH DOSIS PUPUK KASGOT DAN NPK TERHADAP PERTUMBUHAN DAN HASIL TANAMAN PADI (Oryza sativa L.) VARIETAS MENTIK WANGI - -, Cindhea Niarsanti; Yekti, Maryani; Djoko Heru, Pamungkas (Universitas Sarjanawiyata Tamansiswa, 2024)
This study aims to examine the effect of doses of cassava and NPK fertilizers on the growth and yield of rice (Oryza sativa L) of Mentik Wangi variety. This research was carried out in September - February 2022 at the Makmur Sustainable Village Agricultural Training Center. This research was conducted with a factorial complete randomized block design (RAKL) experiment with 3 x 3 replications. It was designed using a factorial complete randomized design (RAKL) with 3 replications. The first factor was (F), which consisted of 3 replicates, namely KI: cassava at a dose of 0 t/ha, K2: cassava at a dose of 1.5 t/ha, K3: cassava at a dose of 2.5 t/ha. The second factor was the type of NPK fertilizer which consisted of 3 replicates, namely P1: phonksa dose of 300 kg/ha, P2: phonksa dose of 400 kg/ha, P3: phonksa dose of 500 kg/ha. Observations made included plant height, number of tillers, number of productive tillers, fresh weight, stalk dry weight, panicle length and number of grain per panicle, 1000 grain weight, weight per hectare. Treatment of cassava and NPK fertilizer doses showed no interaction on growth variables (plant height, number of tillers and number of productive tillers) and yield variables (fresh body weight and number of grain per panicle). The results of the study showed an interaction between the doses of cashew fertilizer and NPK fertilizer on plant height, number of tillers, number of productive tillers, fresh weight of chestnut and number of grain per panicle. The dosage treatment of cassava fertilizer was significantly different on the dry weight of approximation but not significantly different on the weight of 1000 grains, the weight of grain per hectare. The dosage treatment of Phonska NPK fertilizer had a significantly different effect on the approximation dry weight and 1000 grain weight, but not significantly different on panicle length and grain weight per hectare. Keywords : cassava fertilizer, NPK fertilizer, Mentikwangi variety rice